(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Ischemic stroke is caused by the cessation or reduction of perfusion of cerebral arterial vessels. Strokes are the main cause of severe and persistent disability, loss of health and significant economic costs to society. Treatment of ischemic stroke consists of therapy that improves cerebral perfusion in the area of ischemia and therapy that reduces the effects of stroke. An important role in the treatment process is played by diagnosis, early rehabilitation of patients, including nursing, physical therapy and orthotics. The aim of the study is to analyze various methods of treatment and rehabilitation of patients after ischemic stroke and their impact on improving the patient’s functional capabilities. In acute ischemic stroke, the main goal of reperfusion therapy is to quickly restore cerebral blood flow to ischemic brain tissue that is at risk of cerebral infarction. Effective and safe interventions require early comprehensive diagnosis of the nature of the stroke and the patient’s condition. In the modern era of stroke treatment, more and more patients are surviving with varying degrees of disability. A comprehensive rehabilitation program is critical to optimizing post-stroke outcomes. Understanding the natural course of stroke recovery and applying a multidisciplinary approach will increase the chances of successful rehabilitation. The aim of rehabilitation is, among other things, to improve motor function of the upper and lower extremities, reduce aphasia, improve respiratory muscle function, reduce pharyngeal and laryngeal muscle paresis, reduce or eliminate pain, and improve patient well-being. This article provides an overview of current advances in the treatment of acute ischemic stroke, starting with the prehospital stage and in the emergency department, followed by inpatient treatment and early rehabilitation. Early diagnosis, intensive care, and early and comprehensive rehabilitation are crucial in restoring the patient’s ability to work, preventing recurrent stroke, developing complications, and improving the patient’s quality of life.